Autonyms of the Kirat Rai Linguistic Communities: Decoding roots, Meanings, and Identity - Rai, Tara Mani (Kirat Pragya किरात प्रज्ञा, 2025)
This study explores the ‘autonyms’ of the ‘Kirat Rai’ or Rai Kirati linguistic communities through an etymological lens. Autonyms such as roduŋ, rokduŋ, rʌdu, radu, rodʰu, raɖu, rʌ:di, rokoŋ, and kirawa > ki(ra)wa suggest a shared root, *r-duŋ, potentially linked to the Proto Tibeto- Burman (PTB) term *dung (‘to beat, drum, or strike’). However, semantic shifts over time are evident, as seen in Chamling, where *dung(-ma) means ‘to drink.’ This study reveals a geographical distribution and linguistic zones: Western Rai groups (e.g., Bayung/Bahing, Jero/Jerung, Bantawa) retain *r-initial autonyms, while Eastern groups (e.g., Yamphu, Lohorung, Mewahang, Yakkha, Yakthung/Limbu) transition to *y-initial forms. This *r> *y shift extends beyond autonyms to lexical items like ‘salt,’ ‘body,’ and ‘stand.’ Additionally, common affixes (-luŋ, -*wa, -*haŋ, -*riŋ) further connect the linguistic groups, with -luŋ prominently featured in Kulung, Thulung, Lohorung, Sampnag, Dumi, and Lungkhim; -wa in Bantawa, Phangduwa; -haŋ in Mewahang, Newahang; and -riŋ in Sottoring, Kuluring, and Nachhiring, among others. Through a comprehensive literature review and the qualitative research methods, this study underscores how autonyms form identity, history, and cultural resilience, emphasizing their role in preserving linguistic diversity amid global pressures.